2021
DOI: 10.1111/irv.12900
|View full text |Cite
|
Sign up to set email alerts
|

Change in patterns of hospitalization for influenza during COVID‐19 surges

Abstract: Background Hospitalization due to influenza has been stable in recent years. In March 2020, New York was an epicenter for coronavirus disease 2019 (COVID‐19). Because influenza and COVID‐19 present similarly, there were serious concerns that coinfection of these viruses would burden the healthcare system. We compared incidence and outcomes of patients hospitalized with influenza before and during COVID‐19 (seasons 2017–2021). Methods We conducted a retrospective study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Overall, 82.3% of SARS-CoV-2 and influenza co-infected patients were symptomatic at diagnosis [9][10][11][12][13][14][15]27,[60][61][62][63][64][65][66][67]. Despite the differences in terms of transmissibility and incubation period between SARS-CoV-2 and influenza viruses, co-infected patients usually manifested symptoms typical of COVID-19, including (new or persisting) fever (93.2%), cough (97.6%), (new or aggravated) shortness of breath/dyspnea (95.0%), diarrhea (93.8%), myalgia (44.1%), and fatigue (40.3%) [9,10,[12][13][14][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52][53]58,[61][62][63].…”
Section: Sars-cov-2 and Influenza Co-infectionsmentioning
confidence: 99%
“…Overall, 82.3% of SARS-CoV-2 and influenza co-infected patients were symptomatic at diagnosis [9][10][11][12][13][14][15]27,[60][61][62][63][64][65][66][67]. Despite the differences in terms of transmissibility and incubation period between SARS-CoV-2 and influenza viruses, co-infected patients usually manifested symptoms typical of COVID-19, including (new or persisting) fever (93.2%), cough (97.6%), (new or aggravated) shortness of breath/dyspnea (95.0%), diarrhea (93.8%), myalgia (44.1%), and fatigue (40.3%) [9,10,[12][13][14][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52][53]58,[61][62][63].…”
Section: Sars-cov-2 and Influenza Co-infectionsmentioning
confidence: 99%
“…10 Keeping in mind that our data are from the pre-pandemic era, it is possible that the rate of HAII in allo-HSCT patients has dropped even further due to the nationwide hospital reforms in the escalation of airborne and droplet precautions as well as the decrease in hospital visitors. 11 Although the risk of HAII is low in patients admitted for allo-HSCT, our analysis revealed that the patients that do contract influenza are at a significantly higher risk of poor hospital outcomes including death. Therefore, early recognition of symptoms and a low threshold for testing is critical, especially during the flu season.…”
Section: Discussionmentioning
confidence: 73%
“…Our large real‐world data of over 70 000 hospitalizations for allo‐HSCT reported a rate of less than 0.5% of HAIII, which reflects the excellent implementation of preventive strategies, including hand hygiene, gowning, and vaccination of healthcare staff at bone marrow transplant centers across the country 10 . Keeping in mind that our data are from the pre‐pandemic era, it is possible that the rate of HAII in allo‐HSCT patients has dropped even further due to the nationwide hospital reforms in the escalation of airborne and droplet precautions as well as the decrease in hospital visitors 11 . Although the risk of HAII is low in patients admitted for allo‐HSCT, our analysis revealed that the patients that do contract influenza are at a significantly higher risk of poor hospital outcomes including death.…”
Section: Discussionmentioning
confidence: 85%
“…Reductions were also observed for influenza, but evidence of a resurgence was sparse at the time of writing [36][37][38][39]. In Australia, where the seasonal surge in admissions is typically observed in the summer months, surveillance reporting from sentinel hospital sites revealed a return to pre-pandemic levels of hospital admissions for the 2022/23 season (the third since the pandemic began) with a peak in spring [40].…”
Section: Plos Onementioning
confidence: 99%
“…already taxed EDs and healthcare staff. Furthermore, the coexistence of SARS-CoV-2 and influenza in hospitalized patients was rare in the early pandemic, but co-infection is more likely in the upcoming 2022/23 influenza season and the implications of this on viral pathogenesis and patient outcomes remains unclear [38,41,42]. Alleviating strain on the healthcare system may include public health campaigns to promote influenza vaccination, further uptake of anti-RSV vaccination (maternal or among higher-risk infants and children) [43], and exploring RSV vaccination for older adults [44].…”
Section: Plos Onementioning
confidence: 99%